The Secret to Teen Power - Harrington, Paul (Simon and Schuster UK Ltd, 2009)
The Secret to Teen Power explains how the law of attraction can help teens navigate their friendships, relationships, schoolwork, money, and even more global issues like politics and the environment. It all happens through the basic principles outlined in The Secret to Teen Power that will bring happiness and fulfilment for all who embrace it.
Keywords: Body, Mind and Spirit; Juvenile Non-Fiction